Normobaric Hyperoxia Slows Blood–Brain Barrier Damage and Expands the Therapeutic Time Window for Tissue-Type Plasminogen Activator Treatment in Cerebral Ischemia. Issue 5 (May 2015) - Liang, Jia; Qi, Zhifeng; Liu, Wenlan; Wang, Peng; Shi, Wenjuan; Dong, Wen; Ji, Xunming; Luo, Yumin; Liu, Ke Jian
Abstract : Background and Purpose—: Prolonged ischemia causes blood–brain barrier (BBB) damage and increases the incidence of neurovasculature complications secondary to reperfusion. Therefore, targeting ischemic BBB damage pathogenesis is critical to reducing neurovasculature complications and expanding the therapeutic time window of tissue-type plasminogen activator (tPA) thrombolysis. This study investigates whether increasing cerebral tissue PO2 through normobaric hyperoxia (NBO) treatment will slow the progression of BBB damage and, thus, improve the outcome of delayed tPA treatment after cerebral ischemia. Methods—: Rats were exposed to NBO (100% O2 ) or normoxia (21% O2 ) during 3-, 5-, or, 7-hour middle cerebral artery occlusion. Fifteen minutes before reperfusion, tPA was continuously infused to rats for 30 minutes. Neurological score, mortality rate, and BBB permeability were determined. Matrix metalloproteinase-9 was measured by gelatin zymography and tight junction proteins (occludin and cluadin-5) by Western blot in the isolated cerebral microvessels. Results—: NBO slowed the progression of ischemic BBB damage pathogenesis, evidenced by reduced Evan blue leakage, smaller edema, and hemorrhagic volume in NBO-treated rats. NBO treatment reduced matrix metalloproteinase-9 induction and the loss of tight junction proteins in ischemic cerebral microvessels. NBO-afforded BBB protection was maintained during tPA reperfusion, resulting in improved neurological functions, significant reductions in brain edema, hemorrhagic volume, and mortality rate, even when tPA was given after prolonged ischemia (7 hours). Conclusions—: Early NBO treatment slows ischemic BBB damage pathogenesis and significantly improves the outcome of delayed tPA treatment, providing new evidence supporting NBO as an effective adjunctive therapy to extend the time window of tPA thrombolysis for ischemic stroke.